Improved Control of Dynamic Loads Within Hydraulic Systems by Considering Nonlinear Properties of Pipeline Fittings - Zagirnyak, Mykhaylo; Korenkova, Tetyana; Kovalchuk, Viktoriya; Kravets, Oleksii (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
It is shown that the existing methods and technical means of reducing dynamic loads in hydraulic systems do not allow to significantly reduce pressure fluctuations in the hydraulic network. It does not take into account the real hydraulic characteristics of pipeline fittings. The paper is devoted to the development of a method of reducing dynamic loads in the hydraulic systems by forming a non-uniform control law of the variable-frequency electric drive of pipeline fittings, which takes into account the nonlinear dependence of the coefficient of hydraulic resistance on the relative degree of opening of the valve's working body.